KONTRIBUSI KONSEP DIRI DAN KETERLIBATAN ORANGTUA TERHADAP KEMAMPUAN MEMBINA RAPPORT DENGAN TEMAN SEBAYA SERTA IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 29 PADANG - Sari Wardani Simarmata; Marjohan Marjohan; Ali Jamar (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
The ability to build rapport is one of the development tasks that must be endured by the teenagers. This ability is influenced by various factors among which are the factors of self-concept and family factors particularly parental involvement with their children various occasions. This correlation descriptive research also applied quantitative method. The population of this research were students in grade VII and VIII of SMP Negeri 29 Padang. Sample using proportional stratified random sampling technique. The instruments of this research were the Likert scale model. The data obtained were analyzed by using hipotetic mean, simple linier regression, and multiple linier regression. The research finding were: (1) self-concept in average were at high category, (2) parental involvement in average were at high category, (3) the ability to building rapport with peers were at high category, (4) the ability to building rapport with peers explained by the self-concept, (5) the ability to building rapport with peers explained by the parental involvement, and (6) the ability to building rapport with peers explained by the self-concept and parental involvement. The implication of this research may useful to design a guidance and counseling program, especially for personal and social field.Keywords: Self-Concept, Parental Involvement, Rapport